2000
DOI: 10.1046/j.1460-9592.2000.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of oesophageal pH during general anaesthesia with laryngeal mask airway in children

Abstract: We studied the incidence of gastro-oesophageal reflux (GOR) during general anaesthesia with the laryngeal mask airway (LMA) in a paediatric population with two ventilatory regimes: spontaneous breathing and controlled mechanical ventilation (CMV). Thirty children between 6 months and 15 years, ASA I-II, for routine surgery, were randomly assigned in two groups: spontaneous ventilation (n=14), and CMV (n=16). A pH probe was situated in the central third of the oesophagus. Some 66% of the patients breathing spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The rate of reported aspiration appears to be very low although silent gastroesophageal reflux can often occur. It appears that, in reported cases, the diagnosis of reflux had no clinical consequences and compared to facemask ventilation and anesthesia with intubation, the incidence was similar [ 85 , 86 ]. Laryngeal masks have been used for airway management during adenotonsillectomy, tonsillectomy, and adenoidectomy [ 87 ], laparoscopic surgeries (with comparable intragastric pressure to ETT [ 88 ]), during fibreoptic bronchoscopy [ 89 , 90 ], eye surgery [ 91 ], during difficult airway management as a conduit for ETT placement [ 92 , 93 ], and during resuscitation (also in neonates) with no documented difference in outcome compared to ETT use.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of reported aspiration appears to be very low although silent gastroesophageal reflux can often occur. It appears that, in reported cases, the diagnosis of reflux had no clinical consequences and compared to facemask ventilation and anesthesia with intubation, the incidence was similar [ 85 , 86 ]. Laryngeal masks have been used for airway management during adenotonsillectomy, tonsillectomy, and adenoidectomy [ 87 ], laparoscopic surgeries (with comparable intragastric pressure to ETT [ 88 ]), during fibreoptic bronchoscopy [ 89 , 90 ], eye surgery [ 91 ], during difficult airway management as a conduit for ETT placement [ 92 , 93 ], and during resuscitation (also in neonates) with no documented difference in outcome compared to ETT use.…”
Section: Resultsmentioning
confidence: 99%
“…1995; Roux et al. 1999; Cebrian et al. 2000) although other studies demonstrated reflux of gastric contents, at least into the middle or upper oesophagus, to be extremely rare (Joshi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Its large internal diameter allows the use of the fiberoptic bronchoscope without a significant increase in airway resistance (5,6). However, LMA causes gastric insufflations and may produce gastroesophageal reflux (7).…”
Section: Introductionmentioning
confidence: 99%